A note on foreign direct investment (FDI) and industrial competitiveness in Brazil - Régis Bonelli (Institute for Applied Economic Research (ipea), 2015)
This paper addresses a key issue of the link between increased capital inflows through FDI and industrial competitiveness in Brazil. It provides an analysis of the two way relationship which can exist in theory between FDI and competitiveness, as well as some empirical evidence from Brazil in the 1990s. Inflows of FDI to Brazil have increased significantly during the 1990s, and although manufacturing has been losing out in terms of its share of FDI, the stock of foreign capital in the manufacturing sector more than doubled (in current US dollars) between 1990 and 1996. At the same time, rapid growth of manufacturing productivity has been amply documented, in the same period of time. There seems, therefore, to exist a prima facie case for supposing that foreign investment has contributed to increased productivity and competitiveness in Brazil. When looking at disaggregated data within manufacturing which links the growth of competitiveness (whether measured by unit labor costs or export performance) and FDI, however, there does not appear to be a clear cut relationship with either the growth of FDI or the share of foreign capital within different industries. The link applies to some industries, but not to others. In other words: if one interpreted the causation as running in the opposite direction, this evidence would suggest that there is no general tendency for FDI to be attracted primarily to industries where competitiveness is improving most rapidly. This has the implication that rapid productivity growth might be the result of factors other than FDI - like trade liberalization, for instance.
Keywords: 330